1998
DOI: 10.1071/p97092
|View full text |Cite
|
Sign up to set email alerts
|

Application of DFT and EMS to the Study of Strained Organic Molecules

Abstract: Electron momentum spectroscopy (EMS) studies of the valence shells of [1.1.1]propellane, 1,3-butadiene, ethylene oxide and cubane are reviewed. Binding energy spectra were measured in the energy regime of 3 · 5-46 · 5 eV over a range of different target electron momenta, so that momentum distributions (MDs) could be determined for each ion state. Each experimental electron momentum distribution is compared with those calculated in the plane wave impulse approximation (PWIA) using both a triple-ζ plus polarisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…In our previous studies on 1,3‐butadiene,16 [1.1.1]propellane,17 and cubane,18 there were always experimental MDs, for one or two of the respective molecular orbitals, that could be used to make a clear distinction between the quality of the various basis sets and XC functionals that we employed in our DFT calculations 35. Here, however, the situation is not so transparent.…”
Section: Comparison Between Experimental and Theoretical Momentum Dismentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies on 1,3‐butadiene,16 [1.1.1]propellane,17 and cubane,18 there were always experimental MDs, for one or two of the respective molecular orbitals, that could be used to make a clear distinction between the quality of the various basis sets and XC functionals that we employed in our DFT calculations 35. Here, however, the situation is not so transparent.…”
Section: Comparison Between Experimental and Theoretical Momentum Dismentioning
confidence: 99%
“…Experimental validation of Hartree–Fock or density functional basis sets using EMS may provide a route to appropriate basis sets for calculating other types of molecular properties,35 such as molecular geometries, NMR, vibrational spectra, and charge distributions etc. In this work we have taken our “optimum” DFT‐BP/TZVP basis set and used it to derive some of these molecular properties.…”
Section: Molecular Property Informationmentioning
confidence: 99%
“…In the context of the times that these studies were undertaken, they constituted an important source of information that, coupled with quantum theoretical calculations, gave information about the quadratic force fields, normal coordinates, and dipole moment derivatives for these molecules, and allowed some conclusions to be drawn regarding the similarities and dissimilarities of their chemical bonding not only with respect to one another, but also with respect to cyclopropane, which may be considered to be their predecessor molecule. Other work dealt with the photoelectron spectroscopy of propellane [29][30][31][32][33][34][35][36], ab initio calculations of its NMR spectra [37][38][39], and a new theoretical study of its vibrational spectrum and structure [40]. The present account deals primarily with the determination of the ground state constants of propellane, gained from analyzing nine fundamental and four combination infrared bands.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that a wavefunction comprised of these orbitals, since it is derived from experiment, should lead to`more accurate molecular-property information'. In fact, Adcock et al (1998) have performed DFT calculations on these molecules using a variety of basis sets, and have shown that those basis sets which best reproduced the (e, 2e) data were also those which yielded the best molecular geometrical parameters compared to experiment.…”
Section: Methods For Extracting An Experimental Wavefunction From Othmentioning
confidence: 99%